STUDIES OF GENERAL TOYS DESIGN DEVELOPMENT FOR REHABILITATION THERAPY - Nur Saiful Anwar Sainen; Shahrul Azam Abdullah (Journal of Islamic, Social, Economics and Development, 2022)
Stress, injuries, and emotions are typical components that determine the outcome ofthe day in everyday people's lives. This study delivers the pre-process development stage of toyproducts for rehabilitation usage based on actual design requirements to meet the effectiveness,properties, and prototype usage results before introducing the new design to the public. Thefocus of this research is to produce rehabilitation toys based on therapeutic requirements forhand manipulation since that is the key method of stress release. In addition, applying this typeof technique can help decrease general stress as well as provide less energy utilization to thehands, fingers, and joints. Some demand is to improve, strengthen and rehabilitate hands.Secondly, to increase enjoyment of therapeutic aid based on the therapeutic values of theproduct itself.